CONFISCATION THE VEHICLE IN A MISDEMEANOR PROCEEDING - Sladić, Ljubana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The protective measure of confiscation of objects in misdemeanor law can be used to confiscate objects used to commit a misdemeanor, objects intended for the commission of a misdemeanor, and objects resulting from the commission of a misdemeanor. The imposition of this protective measure encroaches on the realization of the property rights of the person who is the owner of the confiscated items, who may or may not be the person who owns the confiscated items. In its practice, the European Court of Human Rights highlighted the criteria that must be taken into account when assessing whether property rights have been violated when imposing this protective measure, and these criteria are respected by the constitutional courts of the countries in the region. The object of confiscation can also be a vehicle, for certain customs misdemeanor, misdemeanor in the field of road transport, but new laws are expected to enter into force in the near future, according to which the vehicle will be confiscated from persons who have committed traffic misdemeanor. At the same time, confiscation of the vehicle will be imposed on persons who are repeat traffic offenders, which actually gives this sanction the character of a punishment, rather than a protective measure.